The Influence Of Leaders’ Knowledge, Skil, And Ability On The Performance Of The Community Satisfaction Index - Rahmad; Diga Putri Oktaviane; Wahib Assyahri; nasfi, nasfi (Adpebi International Journal of Multidisciplinary Sciences, 2024)
The object of this research is the Agam Regency Community Welfare Index (IKM), to examine the influence of Leadership Knowledge, Skill and Ability on Performance in Agam Regency SMEs. The aim of this research is to determine how this model can provide a more precise picture of the causal relationship between Leadership Knowledge, Skill, Ability and Performance. the research sample was 100 employees of IKM Agam Regency, taken from business units engaged in manufacturing such as the production of crafts, food, bags, shoes, crackers and garments. Research data analysis is a structural equation model with the SPSS application program to test the 4 (four) hypotheses that have been developed, the relationship that has been hypothesized is a causal relationship. The results of the proposed hypothesis are accepted, the significance value of the Knowledge variable (X1) is 0.031, the significance value of the Skill variable (X2) is 0.028 and the significance value of the Ability variable (X3) is 0.046, then it is proven that if the significance value (sig) or the probability value is smaller than the significance level used (= 0.05), it can be concluded that there is a significant influence of the Knowledge (X1), Skill (X2) and Ability (X3) variables on Performance in IKM Agam Regency.